Common AAV gene therapy vectors show nonselective transduction of ex vivo human brain tissue - JP McGinnis; Joshua Ortiz-Guzman; Maria Camila Guevara; Sai Mallannagari; Benjamin D.W. Belfort; Suyang Bao; Snigdha Srivastava; Maria Morkas; Emily Ji; Angela Addison; Evelyne K. Tantry; Sarah Chen; et al. (Molecular Therapy: Methods & Clinical Development)
The ability to deliver a therapeutic sequence to a specific cell type in the human brain would make possible innumerable therapeutic options for some of our most challenging diseases; however, studies on adeno-associated virus (AAV) vector tropism have generally relied on animal models with limited translational utility. For this reason, establishing the tropism of common adeno-associated virus (AAV) vectors in living human brain tissue serves as an important baseline for further optimization, as well as a determination of human brain cell types transduced by clinically approved gene therapy vectors AAV2 and AAV9. We have adapted an ex vivo organotypic model to evaluate AAV transduction properties in living slices of human brain tissue. Using fluorescent reporter expression and single-nucleus RNA sequencing, we found that common AAV vectors show broad transduction of normal cell types, with protein expression most apparent in astrocytes; this work introduces a pipeline for identifying and optimizing AAV gene therapy vectors in human brain samples.